Waterproof, Breathable, and Antibacterial Self‐Powered e‐Textiles Based on Omniphobic Triboelectric Nanogenerators - Sala de Medeiros, Marina; Chanci, Daniela; Moreno, Carolina; Goswami, Debkalpa; Martinez, Ramses V. (Advanced functional materials, 2019)
Multifunctional electronic textiles (e‐textiles) incorporating miniaturized electronic devices will pave the way toward a new generation of wearable devices and human–machine interfaces. Unfortunately, the development of e‐textiles is subject to critical challenges, such as battery dependence, breathability, satisfactory washability, and compatibility with mass production techniques. This work describes a simple and cost‐effective method to transform conventional garments and textiles into waterproof, breathable, and antibacterial e‐textiles for self‐powered human–machine interfacing. Combining embroidery with the spray‐based deposition of fluoroalkylated organosilanes and highly networked nanoflakes, omniphobic triboelectric nanogenerators (RF‐TENGs) can be incorporated into any fiber‐based textile to power wearable devices using energy harvested from human motion. RF‐TENGs are thin, flexible, breathable (air permeability 90.5 mm s−1), inexpensive to fabricate (<0.04$ cm−2), and capable of producing a high power density (600 µW cm−2). E‐textiles based on RF‐TENGs repel water, stains, and bacterial growth, and show excellent stability under mechanical deformations and remarkable washing durability under standard machine‐washing tests. Moreover, e‐textiles based on RF‐TENGs are compatible with large‐scale production processes and exhibit high sensitivity to touch, enabling the cost‐effective manufacturing of wearable human–machine interfaces. Any conventional garment or textile can be transformed into a waterproof, breathable, antibacterial, and self‐powered e‐textile by embroidering over their surface omniphobic triboelectric nanogenerators (RF‐TENGs) with highly networked silver nanoflake electrodes. The high output power density and touch sensitivity of RF‐TENGs and their compatibility with large‐scale production processes enable the cost‐effective fabrication of washable e‐textiles for emerging human–machine interface applications.